Association between central blood pressure, arterial stiffness, and mild cognitive impairment. Issue 1 (December 2017) - Suleman, R.; Padwal, R.; Hamilton, P.; Senthilselvan, A.; Alagiakrishnan, K.
Abstract Background To determine the relationship between central blood pressure (CBP) indices and mild cognitive impairment (MCI) in adults over the age of 50. Methods A cross-sectional study conducted using a non-invasive SphygmoCor XCEL device. CBP indices and brachial blood pressure were measured in 50 inpatients and outpatients. MCI was assessed using the Montreal Cognitive Assessment (MoCA) instrument and by the European Consortium Criteria (ECC). Results Seventy-six percent of subjects had hypertension, and 52% were diagnosed as having MCI using the ECC. No significant association was found between any of the measured blood pressure variables and global cognition. A significant relationship was observed between augmentation index (AI) and abnormal clock-drawing (p  = 0.04) and language (p  = 0.02), and between pulse pressure amplification (PPA) and language (p  = 0.03). Conclusion CBP indices like AI and PPA, which are markers of vascular stiffness, are associated with poor executive function and language cognitive domain deficits.